The Paradox of Global Civil Society - Dzwończyk, Joanna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
The article presents the issue of global civil society, which is often regarded as a kind of remedy for global problems. It has been pointed out that civil society is inextricably linked with the institution of the state, as well as democracy, which is not conducive to globalisation. As a strictly verbal structure, the global civil society cannot actually be brought into existence, mainly due to the lack of a universal / global axiological foundation. Referring to attempts to create a global civil society, the author points out that it can become a construct that exists ostensibly to address problems which could be addressed by entities with a real ability to act, but which cannot or do not want to. These are problems best not ignored. Referring to Roland Robertson’s concept of glocalisation, I stress the need to re-evaluate the local-global relation, which I believe will reduce the negative effects of globalisation through the local activities (i.e. operating at the level of the nationstate) of civil societies.